The Academic Leadership of Executives that Affects Proactive Learning Management of Educational Institutions under Nakhonphathom Vocational Education Office - Rungkhuha, Krissada; Jinadattiyo, Phramaha Kraiwan (Journal of Dhamma for Life, 2025)
This research article aims to (1) study the academic leadership of administrators under the Office of Vocational Education, Nakhon Pathom Province, (2) examine the active learning management of educational institutions under the same office, and (3) investigate the impact of administrators’ academic leadership on active learning management in these institutions The sample group consisted of 11 educational institutions under the Office of Vocational Education, Nakhon Pathom Province, with a total of 242 respondents. A questionnaire was used as the research instrument. Data analysis was conducted using statistical software, employing frequency, percentage, arithmetic mean, and standard deviation. Hypothesis testing was conducted using stepwise multiple regression analysis The research findings revealed the following : 1. The overall level of academic leadership of administrators under the Office of Vocational Education, Nakhon Pathom Province, was high. When considering individual aspects, all aspects were at a high level, ranked from highest to lowest as follows: promoting a learning atmosphere, supervision of teaching, curriculum and instructional management, monitoring student progress, and defining the institution’s mission 2. The overall level of active learning management in educational institutions under the Office of Vocational Education, Nakhon Pathom Province, was high. When considering individual aspects, all aspects were at a high level, ranked from highest to lowest as follows: student participation in learning, engagement in activities such as reading, discussion, and writing, self-directed knowledge acquisition, attitudes, values, and experiences, development of thinking skills including analysis, synthesis, and evaluation, and emphasis on activities that develop students’ skills and concepts 3. The analysis of the impact of administrators’ academic leadership on active learning management in educational institutions under the Office of Vocational Education, Nakhon Pathom Province, was statistically significant at the 0.05 level. The most influential factors were ranked as follows: curriculum and instructional management, supervision of teaching, monitoring student progress, and promoting a learning atmosphere. The multiple correlation coefficient (Multiple R) was 0.883, and these variables collectively predicted active learning management in educational institutions under the Office of Vocational Education, Nakhon Pathom Province, by 78.0% (R² = 0.780). The regression equations can be expressed as follows: Forecast equations in raw score form y ̂tot = .131 + .047 (X2) + .048 (X5) + .052 (X4) + .062 (X3) (R2 = .780) Forecast equations in standard score form z ̂y = .170 (zx3) + .240 (zx2) + .257 (zx4) + .307 (zx5) (R2 = .780).